Archives & information in the Early Modern World - Corens, Liesbeth; Peters, Kate; Walsham, Alexandra, 1966- (Oxford : Oxford university press, 2018)
Investigating the relationship between archives and information in the early modern world, this latest collection of essays edited by Kate Peters, Alexandra Walsham, and Liesbeth Corens explores every aspect of record keeping; from the proliferation of physical documentation between the sixteenth and eighteenth centuries to the implication of archives in patterns of statecraft.